Sustaining creative technology entrepreneurship: the role of entrepreneurship development services at public universities in Malaysia - Mhd. Sarif, Suhaimi; Ismail, Yusof (2013)
The global debt crises and high unemployment rates have sparked the third wave of economic recession. A more sustainable solution is required to address the serious economic situation. Most policy makers are convinced to use entrepreneurship as a catalyst to sustain the economic growth and employment opportunities. In any economy, policies on social, political, technology and economics should encourage long term economic growth. As for dynamic economic situation, creative technology entrepreneurship becomes a feasible alternative. A creative technology entrepreneurship provides the ‘sustainability’ feature to face the continuous uncertainty. In doing so, creative technology entrepreneurship education plays significant roles in providing university students not only with formal training but also hands-on knowledge and competency to handle creative technology entrepreneurship. The primary objective of this study is to explore feasible alternatives to address economic uncertainty and roles of entrepreneurship development services at public universities. The study interviewed twenty (20) informants - consist of policy makers, lecturers, and entrepreneurship trainers to explore the roles of entrepreneurship development services at public universities in Malaysia. The results of the study showed that the role of entrepreneurship development services has been formally shaped to meet the requirements of the formal tertiary education programme, which may hinder creative technology entrepreneurship development. The study suggests a larger size of informants and a greater scope of the study to obtain more robust, comprehensive and generalizable results.